BIOMECHANICAL ANALYSIS OF THE STRIKING TECHNIQUE GYAKU-TSUKI IN SPORT KARATE (American Journal of Pedagogical and Educational Research, 2023)
This article presents a biomechanical analysis of the gyaku -tsuki (reverse straight punch) striking technique, one of the basic and most frequently used techniques in sport karate. It examines the kinematic and dynamic characteristics of the movement, the sequence of body movements, and the specifics of muscle and musculoskeletal system function. The analysis is conducted from the perspective of sports biomechanics principles, including the concepts of the kinematic chain, force impulse, and motor optimization. The data obtained allow us to identify key factors in striking effectiveness and can be used in training to improve performance and reduce the risk of injury.